Untargeted metabolomic evaluation of mango bagasse and mango bagasse based confection under simulated colonic fermentation - Herrera-Cazarez, L. Abril (2019)
The aim of this work was to obtain a deeper knowledge of the volatile organic metabolites (VOMs) from mango bagasse (MB) and a MB (20%)-based confection (MBC). The time-trend (0–24 h) production of short-chain fatty acids (SCFA) and metabolites from the non-digestible fraction of MB and MBC, was analyzed by untargeted metabolomics under simulated colonic fermentation. MB and MBC had a particular soluble/insoluble dietary fiber ratio (0.71 and 0.53). Butyrate and acetate were more abundant (MB > MBC) after 0–12 h, than propionate (MB = MBC) after 12–24 h. Different VOMs were identified by HS-SPME-GC–MS in MB (n = 131) and in MBC (n = 73). PLS-DA/OPLS-DA allowed to detect the most contributing VOMs to the fermentation pattern; different metabolomic signatures were obtained for MB (SCFA and their esters) and MBC (phenol and complex fatty acids), in a substrate-dependent manner. The untargeted approach revealed that the VOMs profile is dependent of the food matrix